Adaption Blockchain Technology in Patient Health Records in Saudi Arabia - Reem ALANAZI (Communications of International Proceedings, 2022)
People's health depends on having an up-to-date personal health record (PHR) system. In the e-Health and m-Health age, achieving a trustworthy PHR system is still a problem due to data integration from various EHRs, data interoperability, and ensuring that access to data is completely within the control of the patient. The idea of blockchain to power personal health records (PHRs) is highly interesting in this regard. The present study is conducted to investigate the potential role as well as influence of blockchain technology in patient health records management. A mixed-methods approach is followed for that purpose based on expert interviews and a quantitative survey.  This study indicates that a private blockchain network may exchange PHR data. Many changes are needed before a blockchain-based Personal Health Record (PHR) platform can be utilized in reality, including reductions in data size, better security of personal information and lower running expenses.